2020
DOI: 10.21203/rs.2.21791/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long term outcomes of Burch colposuspension and transobturator tape and single incision needleless (DynaMesh®- SIS minor) for the surgical treatment of female stress urinary incontinence patients who underwent combined pelvic reconstructive surgery or hysterectomy

Abstract: Background Women with SUI often require combined pelvic reconstructive surgery because of sharing risk factors of pelvic relaxation. The aim of this study was to evaluate the efficacy of Burch colposuspension, the transobturator tape (TOT), and single incision needleless (DynaMesh®- SIS minor) procedures in patients with SUI who also underwent combined pelvic reconstructive surgery or hysterectomy. Methods We carried out a prospective cohort study that included 142 patients who underwent Burch colposuspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Several observational and randomized studies have showed similar eficacy and lower morbidity for MUS procedures compared to Burch colposuspension. 8 9 10 17 Others have cited that there was no statistically significant difference in subjective cure rates, but the objective cure rates tended to be higher for MUS. 19 20 21 22 Even if the definition of objective cure varied widely between available studies, many of them still report that MUSs (retropubic slings or transobturator slings) are superior to Burch colposuspension surgery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several observational and randomized studies have showed similar eficacy and lower morbidity for MUS procedures compared to Burch colposuspension. 8 9 10 17 Others have cited that there was no statistically significant difference in subjective cure rates, but the objective cure rates tended to be higher for MUS. 19 20 21 22 Even if the definition of objective cure varied widely between available studies, many of them still report that MUSs (retropubic slings or transobturator slings) are superior to Burch colposuspension surgery.…”
Section: Resultsmentioning
confidence: 99%
“…19 20 21 22 Even if the definition of objective cure varied widely between available studies, many of them still report that MUSs (retropubic slings or transobturator slings) are superior to Burch colposuspension surgery. 10 17 23 24 According to those outcomes, patients receiving midurethral tapes have significantly higher overall and objective cure rates than those receiving Burch colposuspension. In addition, in a survey among professionals, Burch colposuspension would have been chosen only by a minority of surgeons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation